POPULATION ASSESSMENT OF PRAWN CRYPHIOPS CAEMENTARIUS ON RIVERS OF THE SOUTH COAST OF PERU - Wasiw G., José (2015)
Fisheries and biological aspects of the freshwater prawn Cryphiops caementarius are reported based on surveys in the Ocoña, Majes-Camana, and Tambo rivers in the period September-December 2013. A small fraction of the population showed sizes larger than 120 mm, where the largest individuals were found in the Majes-Camana river (mode: 79 mm). There were a higher proportion of females in the Majes-Camana river, predominance of gonads in the incipient stage of maduration in individuals of the Ocoña and Tambo rivers, higher density (individuals/m2) and higher biomass (g/m2) in the lower altitudinal strata, and larger concentration rates in the Majes-Camana and Tambo rivers. Besides, the main physicochemical parameters of water quality showed favorable conditions for the prawn population development.